2021
DOI: 10.1039/d0ob02299c
|View full text |Cite
|
Sign up to set email alerts
|

Silicon phthalocyanines: synthesis and resurgent applications

Abstract: Their unique axial bonds and NIR optical properties have made silicon phthalocyanines (SiPcs) valuable compounds. Herein, we present key synthetic strategies and emerging applications of SiPcs over the past decade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 127 publications
1
52
0
Order By: Relevance
“…Both π-π and electrostatic interactions were involved in the binding of Pcs tetrasulfonate derivatives to recombinant hamster prion protein [18]. It is tempting to speculate that two hydroxyl groups of SiPc(OH) 2 (SO 3 ) 1-3 which are protruding above and below the planar Pc molecule and are known to prevent its self-aggregation may also prevent its π-π interactions with PrP TSE [27]. The lack of local O 2 ( 1 ∆ g ) production, then, may make SiPc(OH) 2 (SO 3 ) 1-3 the least effective derivative in removing PrP TSE epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Both π-π and electrostatic interactions were involved in the binding of Pcs tetrasulfonate derivatives to recombinant hamster prion protein [18]. It is tempting to speculate that two hydroxyl groups of SiPc(OH) 2 (SO 3 ) 1-3 which are protruding above and below the planar Pc molecule and are known to prevent its self-aggregation may also prevent its π-π interactions with PrP TSE [27]. The lack of local O 2 ( 1 ∆ g ) production, then, may make SiPc(OH) 2 (SO 3 ) 1-3 the least effective derivative in removing PrP TSE epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies investigated the in vitro activity of silicon Pcs (SiPcs) formulations against HeLa cells. Unlike most other Pcs, SiPcs possess two additional axial bonds that reduce aggregation in solution and can be synthetically tailored, thereby creating further scope for modulation of optical, chemical, and electronic properties [198]. The results of both studies [173,184] were very promising as they showed that SiPcs presented high photo cytotoxicity against HeLa cells and were non-cytotoxic/low-cytotoxic in the dark.…”
Section: Silicon Pcs (Sipcs)mentioning
confidence: 99%
“…[1][2][3][4] Silicon phthalocyanines (SiPcs) are a promising class of ternary additive due to their low manufacturing cost, industrial abundance and ability to efficiently transport electrons. [5][6][7] Bis(trihexylsilyl) SiPcs ((3HS) 2 -SiPc) and bis(tri-butylsilyl) SiPcs ((3BS) 2 -SiPc) were previously employed as a ternary additive in poly(3-hexylthiophene):phenyl-C 61 -butyric acid methyl ester (P3HT:PC 61 BM) bulk heterojunction (BHJ) OPV devices and provided a 20% increase in power conversion efficiency due to the additional absorption at 685 nm 8,9 Following these initial studies, researchers have explored engineering new SiPcs through increasing the conjugation of the axial groups with pyrenes to improve absorption in the UV region 10,11 as well as increasing the conjugation of the macrocycle to increase absorption in the NIR region. [12][13][14] SiPcs have even been modied to impart both additional photogeneration and increased device stability through active layer crosslinking.…”
Section: Introductionmentioning
confidence: 99%